Double Pre-Bending of an Intramedullary Nail Is the Minimal Invasive Osteosynthesis Solution for Dia-Metaphyseal Fractures of the Radius in Children: Technical Note and Case Series - Carsten Krohn (MDPI AG, 2022)
Whereas in paediatric traumatology for diaphyseal fractures of the radius (intramedullary nail), as well as metaphyseal fractures (K-wire), minimal invasive methods for osteosynthesis were established as gold standard, the ideal osteosynthesis of fractures of the dia-metaphyseal area remains controversial. In this article, the author describes his own minimal invasive technique, using an intramedullary nail that must be pre-bent twice to achieve a stable reduction, with three-point support. The material used for this new surgical technique is an ordinary intramedullary nail. If not available, the operation can also be performed with a sufficiently lengthy K-wire. The intramedullary nail needs to be pre-bent twice, which follows a standardised procedure. A small case series is included to visualise the scope of this minimal-invasive method.